Interleukin-2 plus ribavirin versus interferon-α-2b plus ribavirin in patients with chronic hepatitis C who did not respond to previous interferon-α-2b treatment - Malaguarnera, Mariano; Pistone, Giovanni; Neri, Sergio; Romano, Marcello; Brogna, Alfio; Musumeci, Salvatore (BioDrugs : clinical immunotherapeutics, biopharmaceuticals, and gene therapy, 2004)
Background: Interferon (IFN)-α-2b therapy has been shown to improve clinical conditions of patients with chronic hepatitis C. Several studies showed that the addition of ribavirin to IFNα-2b greatly improved the biochemical as well as the virologic and histological response rate in patients with chronic hepatitis C. The aim of this study was to evaluate biochemical, virologic, and histological responses as well as adherence to a treatment employing ribavirin plus low doses of recombinant interleukin (IL-2) or IFNα-2b in subjects with chronic active hepatitis C, which relapsed or did not respond to previous treatment with interferon alone. Patients and methods: We evaluated all 75 consecutive adult patients with chronic hepatitis C admitted to our department, who were previously treated with one course of recombinant or lymphoblastoid IFNα-2b (3 million to 6 million IU three times a week for at least 4 months), and either relapsed or did not respond to this treatment. Sixty patients met the inclusion criteria for enrollment in our study. Randomization was performed on the basis of a computer-generated list. The treatment schedule was based on subcutaneous administration of recombinant IFNα-2b (Intron® A) at a dosage of 3 million IU every day, or IL-2 (aldesleukin) at a dose of 1 million IU every day, with oral ribavirin administered 400mg twice daily (morning and night) [for patients weighing <75kg] or 500mg twice daily (for those weighing≥ 75kg). The planned treatment period was 6 months. Results: Both IFN and IL-2 treatment groups achieved a significant biochemical response with respect to baseline values at the end of the treatment (p < 0.0001 for both) and at the end of the follow up (p < 0.001 for both). The differences between the two groups at the end of treatment and at the end of the follow up were significant (p < 0.04 and p < 0.003 respectively) in favor of IL-2-treatment. The virologic response rate for IL-2-treated patients was significantly higher than for IFN-treated patients at months 3 (p < 0.05) and 6 (p < 0.05) of the treatment. Both groups showed significant improvement in histological activity index with respect to baseline values, but the difference between the groups was not significant. No withdrawals have been registered. Conclusion: The combination of IL-2 and ribavirin seems to increase the probability of a sustained biochemical and virologic response in patients with chronic hepatitis C that is unresponsive to IFN. Our study showed that IL-2 plus ribavirin may provide a clinically important option that appears to be well tolerated and effective in patients with chronic hepatitis C virus infection.